Aplikasi Pengontrolan Programmable Logic Controller Terhadap Smart Traffic Light Pada Simpang Tiga - Yudha Hadi Martha; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Nowdays traffic jam oftenoccurs at the crossroad of traffic light in Pekanbaru. It is caused by the increasing number of two-wheeled vehicles, four-wheeled vehicles, or more. Besides at the traffic light used are also still active based on the length of time that has been set by the system.it makes more of the long quene on that road, because the time needed for green lamp to be active at every intersection is same. Therefore, it is needed a controlling of traffic lights between can detect any traffic jam. This research makes anapplications of Smart Light Traffic(STL) control system between Tengku Bey street – Kaharudin Nasution street Pekanbaru, crowded uses LD Microsoftware. STL controllingsystem controls the functional length green lamp based on crowded a reading of the traffic light on the thirdcrossroads by proximity sensors. Traffic light active sequence is equal to clockwise traffic light will be actively started with red lamp, followed green lamp and yellow. For normal condition of STL, green lamp actives 20s, yellow lamp3s, and red lamp actives 49s.in peak condition of STL, green lamp actives longer 5s (be 25s), yellow lamp actives still 3s, and red lamp actives 59s. This program works as its framework. . Keywords: Smart traffic light,LD Micro software , Proximity sensor, Traffic light, Programmable Logic Control.